POST-PANDEMIC CURRICULUM ADAPTATION IN THE DIGITAL LEARNING ERA - Nabila Nabila; Melinah Diana Putri (PT. Intelek Cendikiawan Nusantara, 2025)
The COVID-19 pandemic significantly transformed educational practices and accelerated the adoption of digital learning across all levels of schooling. As institutions transition into the post-pandemic era, curriculum adaptation is essential to ensure that learning remains relevant, flexible, and aligned with technological advancements. This study aims to develop a conceptual model for curriculum adaptation in the digital learning era using the ADDIE instructional design framework, which consists of the Analyze, Design, Develop, Implement, and Evaluate phases. The research employed a Research and Development (R&D) approach supported by literature analysis and expert review to refine the proposed adaptation model. The findings indicate that curriculum redesign in the post-pandemic context requires the integration of digital literacy, learner-centered strategies, technology-enhanced assessments, and flexible blended learning. The ADDIE-based model developed in this study provides a systematic structure to guide educators and curriculum developers in modifying curriculum components to better support digital learning environments. This research strengthens curriculum innovation efforts and offers practical recommendations for improving instructional planning in the post-pandemic digital era